Introducing the ‘female pilgrim’s gaze’ on a pilgrimage to Uman in Ukraine - Marchenko, Alla (Journal of contemporary religion, 2025)
This article employs the example of the most visited Jewish shrine in Europe today, located in Uman (Ukraine), to introduce the concept of the ‘female pilgrim’s gaze’. The research explores the characteristics of this gaze, examining to what extent they support or contest the established meanings of the Jewish pilgrimage. Particular attention is paid to five characteristics of the ‘female pilgrim’s gaze’: taking a more private view of the pilgrimage, placing an emphasis on one’s connections with other women, declaring the uniqueness of one’s own experience, emphasising inconvenience and physical hardship, framing one’s trip as ‘spiritual’. The existence of the ‘female pilgrim’s gaze’ also questions the stereotype that ‘Uman is a man’s territory’, as it sheds light on the specific relevance of the pilgrimage to Uman for women.